IMPLEMENTASI SISTEM INFORMASI GEOGRAFIS BIDANG PENDIDIKAN (Studi Kasus Kecamatan Tugu Semarang) - Hendri Rasminto (STEKOM PRESS, 2019)
At present the information of schools in various fields of education in the Tugu sub-district is still incomplete that only covers the TK / RA and SD / MI levels so that the wider community has not been able to obtain information on the level of education at SMP / MTs, SMA / SMK / MA and Higher Education, and to get this information the public must come directly to the Semarang City Education Office to find the data needed. The public cannot know quickly if there is a change in data or if there is a construction of a new school because the information is only written on the sub-district bulletin board. Tugu sub-district is a sub-district in the city of Semarang, Central Java province. Tugu sub-district region is bordered by the Java sea in the north, in the east by West Semarang Sub- district, in the south by Ngalian sub-district, and in the west by Kendal district. Tugu sub-district has an area of ± 3.444,22 Ha hectares, consisting of 7 kelurahan, namely Jrakah, Tugurejo, Karanganyar, Randugarut, Mangkang Wetan, Mangunharjo and Mangkang Kulon [7] Various suggestions appear to help equip human work to be more efficient and productive, we need a system that can help the work needed by a web-based Geographic Information System. Geographic Information System is a computer-based system for processing data or information that has a geographical dimension [1]. The program used in research uses the PHP programming language, JAVA SCRIPT because this program can be run on a server and is quite reliable using a MySQL database. [3]